Potential biomarkers: Identifying powerful tumor specific T cells in adoptive cellular therapy - Ge, Wu; Dong, Yuqian; Deng, Yao; Chen, Lujuan; Chen, Juan; Liu, Muqi; Wu, Jianmin; Wang, Wei; Ma, Xiaoqian (Frontiers in Immunology, 2022)
Tumor-specific T cells (TST) are essential components for the success of personalized tumor infiltrating lymphocyte (TIL) -based adoptive cellular therapy (ACT). Therefore, the selection of a common biomarker for screening tumor-specific T cells in different tumor types, followed by ex vivo expansion to clinical number levels can generate the greatest therapeutic effect. However, studies on shared biomarkers for tumor-specific T cells have not been realized yet. In this review, we summarize the similarities and differences of some biomarkers in tumor-specific T cells that deserve to be studied in the last five years and the advantages of combining different biomarkers. In addition, we discuss the possible shortcomings of current biomarkers and highlight strategies to identify tumor-specific T cells accurately using intercellular interactions. Finally, the development of tumor-specific T cells in personalized TIL-based ACT toward broader clinical applications has been prospected.